The ever-reviving phoenix Jesuits in Hungary - Mihalik, Béla Vilmos 1984- (Brill, 2024)
"For more than four and a half centuries, the Jesuits in Hungary were forced to repeatedly recommence their activities due to wars, uprisings, and political conflicts. The Society of Jesus first settled in Hungary in 1561 during the period of Ottoman conquest. Despite their difficulties in a war-torn country, a network of Jesuit colleges was established as part of the Austrian Province, and the eighteenth century was a period of cultural and scientific prosperity for the Jesuits in Hungary. The Suppression of 1773, however, abruptly suspended this tradition for eighty years. After they resettled in Hungary in 1853, the Jesuits searched for new ways of apostolic work. The independent Hungarian Jesuit Province was established in 1909. The totalitarian regimes of the twentieth century posed fresh challenges. During the Communist period, the Hungarian Jesuit Province was forced to split up into two sections. The Jesuits in exile and those who remained in Hungary were reunited in 1990."